The mediating infuence of entrepreneurial empowerment on the linkage between Islamic microfinance services and clients’ well-being in Malaysia: perceived assesment of service provider - Usman, Abubakar Sadiq (2017)
Understanding clients’ well-being from the perspective of service provider is important in Islamic microfinance services. The objective of the study was to examine the relationship between Islamic microfinance services with entrepreneurial empowerment and clients’ well-being. Three research questions and seven hypotheses were formulated to guide the study. The study covered within peninsular Malaysia. The sample was chosen from east coast states of Malaysia (Pahang, Terengganu and Kelantan states) because these states attracted more than 50% of funds disbursement by Amanah Ikhtiar Malaysia (AIM). The study population was 400, defined as a group of employees of Amanah Ikhtiar Malaysia (AIM) who are directly involved in the delivery of Islamic microfinance services. This comprised of branch manager and nine (9) members of staff from operations department in each of the 40 branches in the region. The sample for the study was 291 survey respondents from these staff of Amanah Ikhtiar Malaysia (AIM). A structured questionnaire consisting of closed-ended multiple choice questions was presented to the respondents, selected by a stratified and simple random sampling. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and Analysis of Moment Structures (AMOS) were used to test the validity and reliability of the conceptual research model. The survey results supported four hypotheses, confirming that Islamic microfinance services have positive relationship with entrepreneurial empowerment. The results rejected three hypotheses on the relationship between Islamic microfinance services and clients’ well-being. The unique finding of the study is that, it has espoused the importance of entrepreneurial empowerment as a full mediator towards achieving clients’ well-being. The researcher concludes that Islamic microfinance services can improve clients’ empowerment and well-being by emphasising human, physical and social capital development.